2021
DOI: 10.3390/ijms22168972
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Starch Metabolism in Pea Seeds towards Tailoring Functionality for Value-Added Utilization

Abstract: Starch is the most abundant storage carbohydrate and a major component in pea seeds, accounting for about 50% of dry seed weight. As a by-product of pea protein processing, current uses for pea starch are limited to low-value, commodity markets. The globally growing demand for pea protein poses a great challenge for the pea fractionation industry to develop new markets for starch valorization. However, there exist gaps in our understanding of the genetic mechanism underlying starch metabolism, and its relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 165 publications
(268 reference statements)
0
24
0
Order By: Relevance
“…Besides protein, legumes, especially peas, have a high content of starch (≈30%-50%) [2,3] which is assumed to consequently become available in larger quantities. [1,4] Starch is a polymeric carbohydrate which consists of two major fractions. Amylose (AM), a mainly linear polymer of anhydroglucose units conjoint with 𝛼-1,4glycosidic bonds, and amylopectin (AP), which refers to a highly branched polymer with 𝛼-1,4-glycosidic bonds (linear chain segments) and 𝛼-1,6-glycosidic bonds (branching points).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides protein, legumes, especially peas, have a high content of starch (≈30%-50%) [2,3] which is assumed to consequently become available in larger quantities. [1,4] Starch is a polymeric carbohydrate which consists of two major fractions. Amylose (AM), a mainly linear polymer of anhydroglucose units conjoint with 𝛼-1,4glycosidic bonds, and amylopectin (AP), which refers to a highly branched polymer with 𝛼-1,4-glycosidic bonds (linear chain segments) and 𝛼-1,6-glycosidic bonds (branching points).…”
Section: Introductionmentioning
confidence: 99%
“…[8,15,[17][18][19] It is also reported that pea starch tends to cause manufacturing problems more often than other starches, rendering its application less attractive. [4,18,20] A possible explanation for these problems is seen in the underestimated variation of the characteristics between different pea starch varieties. These might be bigger than for other sources or more critical to applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pea is the most widely cultivated legume in temperate zones (Wille et al 2021) and forms an integral part of the human diet in many countries for its abundant nutritional value. Pea is an essential source of highquality proteins, starch, micronutrients, dietary bers, phenolic compounds, and antioxidants (Kaur and Dhar 2019; Tarasevičienė et al 2019;Yu et al 2021). However, due to the existence of protease inhibitors such as α-amylase inhibitors, phytic acid, saponin, and other anti-nutritional factors, inappropriate intake of the pea can have adverse effects on human health, which signi cantly limits its application in a broader range (Boukid et al 2021;Qi et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…To fill the gap in our understanding of the genetic mechanisms underlying starch metabolism and its relationship with its physicochemical and functional properties, Yu et al [14] summarized the starch biosynthetic pathway in peas and starch granule structure, and its connection with functional properties and industrial applications. They also described that the identification and characterization of novel genes and novel allelic variations in known genes might provide further gene targets for increasing our understanding of starch metabolism to design multifunctional native pea starch for custom modulating starch composition and structure and, thus, functionality.…”
mentioning
confidence: 99%